PENGARUH LIKUIDITAS, PERTUMBUHAN PENJUALAN, DAN PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PT. ASTRA ISUZU INTERNASIONAL TBK YANG TERDAFTAR DI BEI PERIODE 2009-2017 - REBECCA EVADINE (LP2MTBM MAKARIOZ, 2020)
This research aims to determine the impact of liquidity, sales growth, and turnover of working capital towards profitability atPT. Astra Isuzu International listed on the Indonesia Stock Exchange in 2009-2017. The research methods used byresearchers are quantitative descriptive. Using secondary data. The data collection method is done by literature study. Thestatistical analyses used in this study were classical assumption tests, multiple linear regression analyses, correlation,coefficient of determination, simultaneous hypothesis testing (F test) and partially (Test T). Based on the results of thestudies it can be noted that partial liquidity, the growth of the distribution, and the turnover of working capital affect theprofitability of the company. Simultaneous liquidity, sales growth, and turnover of working capital affect profitability. Thecoefficient of determination test results in 83.4% of the variable profitability variations that can be explained by independentliquidity variables, sales growth and working capital turnover.